Experiencing Land-Based Nourishing: An Indigenous Evaluation of Urban Land-Based Food Education in the Waterloo Region - Peach, Laura (University of Waterloo, 2025)
Background: Across Canada, Indigenous communities have sustained their health and wellbeing through cultural practices enacting their knowledges and intimate connection with the Land. As a health promotion strategy reflecting these concepts of wellbeing, many communities are using Land-based learning models to situate culturally-therapeutic and educational experiences that foster pathways towards wellness. However, few studies have evaluated these activities to determine their success, particularly in urban community contexts and with Indigenous children. Objectives: The purpose of this dissertation research is to examine whether Land-based learning approaches to food education for children within an urban setting enhances participant food literacy. Collaborating with two urban Indigenous organizations in the Waterloo Region, Ontario, Canada, this examination extends across three studies that address more specific questions concerning this phenomenon. Specifically, the objectives of this study were to: develop a culturally and locally responsive evaluation framework for WONAA and WC’s Land-based learning programs with a focus on food education; document and evaluate the process and outcomes of a Land-based learning program among urban Indigenous children; and, synthesize findings across studies to renew the initial co-constructed program theory, examining key lessons from implementing a Land-based food program towards reconceptualizing food literacy within an urban Indigenous context. Methods: Using a community-based Indigenous evaluation approach, the articles of this dissertation use diverse qualitative methods informed by relational Indigenous methodologies and realist philosophy to co-construct a culturally responsive program theory, assess a Land-based pilot program, and synthesize findings to put forth a reconceptualization of food literacy as a community-determined, context-specific health promotion concept. Iterative group discussions, participant observation, and photo elicitation methods were used with purposive samples of Indigenous community experts, program facilitators, and child program participants. Results: Findings from Study 1 report a novel methodological approach using iterative sharing circle conversations with diverse, partner-identified community experts to co-construct a culturally and contextually appropriate program theory as the first step in the wider evaluation project. Guiding conversations through four thematic topics were found to concurrently support the planning of both the program and its evaluation through theory co-construction. An initial program theory is presented as a theory of “Land-based nourishing”, which portrays a nascent process of becoming well with food instead of pre-determined or predictable outcomes to be anticipated at the outset of a program. This iterative conversational method also enabled a reframing of evaluation itself as a cycle of responsibility, which reflects the values of Indigenous organizational partners. These insights were applied in Study 2 to identify the context, mechanisms, and outcomes of Sweetwater Camp, a children’s Land-based pilot program. Evaluation results highlight an emergent program context characterized by a process of “giving over to the land,” in which facilitators responded to unpredictable natural conditions in positively adaptive ways that acknowledged more-than-human actors as program co-facilitators. Key mechanisms delineate “the strength of relational implementation” where Camp activities and participant behaviours established ways of learning through collaborative facilitation and meaningful connection by engaging in risky play and fostering a sense of belonging among child campers. Program outcomes were found to be “whatever, however we were gifted, happened,” denoting the inconclusiveness of early indicators of program impact including participant development of new skills and knowledge and the formation of deepened relationships with all program participants in ways that could not be planned for. The results of Study 3 synthesized findings from the prior two studies to demonstrate the limited relevance and applicability of the conventional term, ‘food literacy’. Rather, participants from both preceding studies renewed the initial conceptualization of “Land-based nourishing” proposed in Study 1. Aggregated data clearly articulate the meaning of this contextual health concept with symbolic representation gleaned from child-produced photographs. Land-based nourishing, as such, was understood as a personally unique process of developing a dignified sense of wellbeing through practicing key relational principles, engaging in a variety of skills and knowledge that respect the Land as the greatest teacher, and cultivating a spiritual link with food itself. Together, these studies chronicle an evaluation journey of co-creating an organizationally distinct Indigenous evaluation approach that captures the strengths of Land-based food programs for urban Indigenous young people. The final article, a discussion paper, reflects on this process by considering current ethical guidance around relational research conduct. In this reflection, several taken-for-granted assumptions and ethical dilemmas are explored and followed with suggestions for navigating and preventing some relational challenges that could be encountered when trying to do Indigenous research ‘in a good way’. Conclusion: The articles included in this dissertation make several methodological, theoretical, and substantive contributions to the literature as well as public health practice and policy by reporting the creation and implementation of a distinct Indigenous evaluation approach. This research used a unique program theory co-construction methodology, assessed an urban Land-based children’s program, and concurrently reconceptualized a nutrition promotion concept reflecting shared community values and context. Jointly, these works demonstrate that relationships matter to nourishing wellness with and through food.
Keywords: Indigenous; land-based; evaluation; food literacy; urban; wellbeing; children